EVALUATION OF THE APPLICATION OF FOOD SAFETY FOR THE HOUSEHOLD INDUSTRY "BREAD ANNI" KARAWANG, WEST JAVA IN THE NEW NORMAL ERA - Milliyantri Elvandari; Risma Rahmatunisa (Proceedings of the 1st International Conference on Social Science (ICSS), 2022)
Maintaining the movement of food along the food chain is an important function that all stakeholders along the food chain need to contribute. Food safety is an important component of any food business in ensuring a food safety culture. One way to attract consumers' attention is to ensure that the food produced is safe for health with a guarantee of cleanliness. One of the food businesses that have promising prospects for their owners is in the bakery sector . The purpose of this study is to identify the application of a food safety system with the GMP system in the Home Industry (IRT) in Karawang . The place where this research was conducted was one of the Karawang home industries. This research was conducted using the field observation method, the research was conducted in August 2022 . Data collection, namely primary data obtained by observation and interviews. Respondents were determined by purposive sampling. The data analysis method used is descriptive analysis. The descriptive analysis in this study includes evaluating the condition of each of the basic GMP requirements. The results of research on food safety in one of the Karawang home industries , namely Roti Anni, found that the application of aspects of food safety according to the GMP system from 13 aspects 1 aspect was very fulfilling, 9 aspects were categorized as fulfilling, 2 aspects were sufficient and 1 aspect was not fulfilled, namely in laboratory checking according to CPPOB